PEMANFAATAN METODE IMPRESIF TERHADAP PROSES PENGEMBANGAN KARAKTER SISWA - Karim, Ahmad Abdul; Firdaus, Muhamad Yuda; Dewi, Rizky Kurnia; Yuliani, Yuliani; Hartati, Dian (Universitas Hamzanwadi, 2021)
Teaching literature during a pandemic can be an alternative in developing character in students. This research is important to do to see the convergence of performances that are usually watched once, but due to digitalization, it is now easier for viewers to enjoy the performance. This study reveals the role and function of virtual drama staging in character building in children during the pandemic. The research data source is the recording of the virtual performance of Theater Comma entitled